2018
DOI: 10.1113/ep086887
|View full text |Cite
|
Sign up to set email alerts
|

UBC‐Nepal expedition: The use of oral antioxidants does not alter cerebrovascular function at sea level or high altitude

Abstract: Hypoxia is associated with an increase in systemic and cerebral formation of free radicals and associated reactants that may be linked to impaired cerebral vascular function and neurological sequelae. To what extent oral antioxidant prophylaxis impacts cerebrovascular function in humans throughout the course of acclimatization to the hypoxia of terrestrial high altitude has not been examined. Thus, the purpose of the present study was to examine the influence of orally ingested antioxidants at clinically relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…While the focus of our investigations was to assess the role of NO in regulating cerebral hypoxic vasodilation, the role of other prototypical vasodilators should not be disregarded. Previous studies conducted in humans have largely demonstrated that neither adenosine, 31 prostaglandins, [32][33][34] or reactive oxygen species, 35,36 are obligatory for cerebral hypoxic vasodilation. However, Harrell and colleagues recently demonstrated that combined prostaglandin synthesis inhibition and ascorbic acid infusion results in a marked blunting of cerebral hypoxic vasodilation in humans (albeit with transcranial doppler blood velocity estimates of CBF), highlighting that 'redundancy' of vasodilatory pathways may underscore the lack of effect from vasodilator pathway blockades typically observed in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…While the focus of our investigations was to assess the role of NO in regulating cerebral hypoxic vasodilation, the role of other prototypical vasodilators should not be disregarded. Previous studies conducted in humans have largely demonstrated that neither adenosine, 31 prostaglandins, [32][33][34] or reactive oxygen species, 35,36 are obligatory for cerebral hypoxic vasodilation. However, Harrell and colleagues recently demonstrated that combined prostaglandin synthesis inhibition and ascorbic acid infusion results in a marked blunting of cerebral hypoxic vasodilation in humans (albeit with transcranial doppler blood velocity estimates of CBF), highlighting that 'redundancy' of vasodilatory pathways may underscore the lack of effect from vasodilator pathway blockades typically observed in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to include a wide range of metrics being utilized from the various groups researching neurovascular coupling, 6 we not only included metrics recommended within the recent guidelines, 6 but also included published neurovascular coupling metrics such as those derived from model systems analysis, 25 area under the curve analysis, 26 discrete time windows, 6 and rapidity of response. 27…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, nitric oxide has also been demonstrated to contribute to hypoxia‐mediated increases in CBF . Based on current and previous data, ROS do not influence hypoxia‐mediated increases in CBF; however, combined ROS suppression and COX inhibition largely attenuates hypoxia‐mediated increases in CBF. These data provide novel insight into human cerebrovascular control during hypoxia by identifying 2 interactive vasodilator mechanisms that may provide therapeutic opportunities to treat cerebrovascular dysfunction linked to ageing, diabetes or other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 76%
“…ROS potentially contribute to vascular control as human studies demonstrate hypoxia increases oxidative stress in the cerebral circulation . While intravenous infusion of the antioxidant ascorbic acid modestly reduces hypoxic cerebral vasodilation, an acute oral antioxidant dose failed to alter cerebrovascular responses to hypoxia . Furthermore, it has been demonstrated that ROS dilate murine pial arterioles, albeit these experiments did not include hypoxia.…”
Section: Introductionmentioning
confidence: 99%